2011
DOI: 10.1007/s12369-011-0111-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on People Living with Seal Robot at Home

Abstract: This study examined people living with Paro, a seal robot, and how they interact with it. Questionnaires were sent along with Paro to the owners who could voluntarily choose to respond. Eighty-five responses were obtained and analyzed in terms of gender, preference for animals, and pet ownership experience. The results showed that for females, besides "can touch and hug," "tactile texture" is also an important reason for keeping Paro. In addition, owners' preference for animals seems to influence how they touc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…1) was developed by Dr. Takanori Shibata of the Intelligent Systems Research institute of the National Institute of Advanced Industrial Science and Technology in Japan. It was designed as a “mental-commitment robot”, that is, its function is solely to interact with people and elicit positive emotions (Shibata et al, 2012). PARO has tactile sensors on its endoskeleton, which is covered in soft fur to promote engagement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) was developed by Dr. Takanori Shibata of the Intelligent Systems Research institute of the National Institute of Advanced Industrial Science and Technology in Japan. It was designed as a “mental-commitment robot”, that is, its function is solely to interact with people and elicit positive emotions (Shibata et al, 2012). PARO has tactile sensors on its endoskeleton, which is covered in soft fur to promote engagement.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, users are likely to have pre-existing notions about the behavior of common household pets such as cats and dogs, and so their expectations may not be met when interacting with their robotic counterparts. In contrast, PARO’s unfamiliar seal-like appearance may allow it to be more easily accepted (Shibata et al, 2012; Shibata and Tanie, 2001). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takanori Shibata, the inventor of the Paro robotic seal, has undertaken various studies into the use and value of his product. One example is the administration of a questionnaire sent with the robot when purchased [20], with a subsequent study comparing video recordings of elderly persons with dementia interacting with Paro versus a stuffed toy lion [21]. …”
Section: Introductionmentioning
confidence: 99%
“…When elderly patients suffering from dementia interacted with Paro for a period of time, their emotional well-being and depression improved. 9,10 Later, Wada et al 11 found that Paro facilitated human interactions rather than replacing them. Also, urine tests indicated that patients' stress levels were decreased after they interacted with Paro.…”
Section: Introductionmentioning
confidence: 99%